The language and literature of the New Testament: essays in honor of Stanley E. Porter's 60th birthday - Porter, Stanley E.; Fuller Dow, Lois K.; Evans, Craig A.; Pitts, Andrew W. (Biblical interpretation series, 2016)
Preliminary Material -- Interdisciplinary New Testament Scholarship: An Introduction to the Research of Professor Stanley E. Porter /Andrew W. Pitts -- 1 Setting Scholarship Back a Hundred Years? Method in the Septuagint Commentary Series /Richard S. Hess -- 2 The Past, Present, and Future of the OpenText.org Annotated Greek Corpus /Christopher D. Land and Francis G. H. Pang -- 3 Computer-Aided Linguistic Analysis for a Single Manuscript Witness: Preparing to Map the OpenText.org Annotation /Catherine Smith and Matthew Brook O’Donnell -- 4 Überlegungen zur angeblichen Textverderbnis von Apg 17,27 (Codex Bezae Cantabrigiensis) und zu Joh 8,25 /Hans Förster -- 5 Restoring a Vernacular Form of the Word for “Glass” in the Text of Revelation /John A. L. Lee -- 6 Sense Units and Manuscript Families: A Test Proposal /Sean A. Adams -- 7 Christian Demographics and the Dates of Early New Testament Papyri /Craig A. Evans -- 8 The Use of Greek in First-Century Palestine: An Issue of Method in Dialogue with Scott D. Charlesworth /Hughson T. Ong -- 9 Grappling with Paul’s Language: How a Greek Might Struggle /R. Dean Anderson -- 10 Exploring Linguistic Variation in an Ancient Greek Single-Author Corpus: A Register Design Analysis of Josephus and Pauline Pseudonymity /Andrew W. Pitts and Joshua D. Tyra -- 11 Οὖν in the New Testament: The Minimal Semantic Contribution of a Discourse Marker /Cynthia Long Westfall -- 12 The Telic Conjunctions of Isaiah 6:9–10 in Mark’s Mythopoeia /Thomas R. Hatina -- 13 Greek Tenses in John’s Apocalypse: Issues in Verbal Aspect, Discourse Analysis, and Diachronic Change /Buist M. Fanning -- 14 The Gospel according to Malachi /Mark J. Boda -- 15 Σημεῖα, Signs, as a Hyperlink between the Fourth Gospel and the Greek Pentateuch /Ronald D. Peters -- 16 The Authentication of John: Self-Disclosure, Testimony, and Verification in John 21:24 /Charles E. Hill -- 17 Getting Along: Politeness Theory and the Gospels /Jonathan M. Watt -- 18 The Structure and Content of Stephen’s Speech compared to Old Testament Credos /Thomas H. Olbricht -- 19 Minding the Gap: Why Paul’s Conversion Matters for Christology /Darrell Bock -- 20 Introducing Foreign Deities: The Documentary Evidence /Eckhard J. Schnabel -- 21 The Apostle of the Heretics? /James D. G. Dunn -- 22 Habakkuk, Paul, and the End of Empire: A Fresh Perspective on Romans 13:1–7 /Nicholas Perrin -- 23 The Apostle and the Doctor: Lloyd-Jones on Romans /Stephen Westerholm -- 24 A Comparison of the Fruit of the Spirit in Galatians 5:22–23 with Ancient Thought on Ethics and Emotion /Craig S. Keener -- 25 To Incline Another’s Heart: The Role of Attitude in Reader Positioning /James D. Dvorak -- 26 “Think” and “Do” Like the Role Models: Paul’s Teaching on the Christian Life in Philippians /Jae Hyun Lee -- 27 Postcolonial Perspectives on Paul’s “Jew-Gentile Problem” /Christopher D. Stanley -- 28 A Reexamination of Paul’s Opponents in Colossians /David L. Mathewson -- 29 First Timothy 5:18 and Early Canon Consciousness: Reconsidering a Problematic Text /Michael J. Kruger -- 30 The Epistle of James and the Maccabean Martyr Tradition: An Exploration of Sacred Tradition in the New Testament /Bryan R. Dyer.